A META-ANALYSIS OF THE DETERMINANT OF THIRD PARTY FUND ON ISLAMIC BANKING IN INDONESIA - Indiastary, Diyas; Suprayogi, Noven; Indrawan, Imam Wahyudi (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2020)
This research attempts to study the determinants of third party funds on the Islamic banking in Indonesia with eight years of research from published journals in Indonesia. To reach the above objectives, investigation to check the relationship between promotion cost, inflation, GDP, interest rate, number of offices, and equivalent rate to third party funds on the Islamic banking in Indonesia is conducted. This research applies the meta-analysis technique to a sample of 34 articles with time variation from 2010-2018. The articles used are selected studies from Sinta Journal and Google Scholar databases. This research shows that promotion cost, number of offices, and equivalent rate have a significant correlation with third party funds on the Islamic banking in Indonesia. Meanwhile, inflation, GDP, and interest rate have no significant correlation with third party funds on the Islamic banking in Indonesia. The Findings from this study imply that if Islamic banks in Indonesia wish to enhance their third party fund, they must focus on internal indicators (promotion cost, number of offices, and equivalent rate), rather than looking at macro indicators.